Does mobile money have a part to play in poverty reduction within South Africa? - Mollagee, Shuaib (Graduate School of Business (GSB), 2025)
There is a growing amount of research that points towards an additional factor capable of increasing inclusive growth and therefore successfully reducing poverty levels within a country, that is, the use of mobile money. With the rise of mobile phone penetration within African countries, its use has gone beyond communication, providing key financial access in the form of phone-based money transfers and storage. The mobile phone has assisted in providing the previously marginalized with more affordable and cost-effective financial services. The population living in poverty also generally lack information vital to the work they do. Whether its market prices, information on new income earning opportunities, or even as simple as up-to date weather reports that could affect their existing job. The lack of up-to-date knowledge adds to their already vulnerable state. Mobile phones assist in providing this information to the poor in cost-effective ways. This study tests whether mobile money has a part to play in poverty reduction, specifically within South Africa. It uses data obtained from FinMark Trust from the 2018 Finscope SA survey. To that end, the Alkire and Santos (2011) method was used to compute a multidimensional poverty index (MPI). Using the MPI, an instrument variable approach was used to treat the endogeneity bias seen by the two-way relationship between poverty and mobile money adoption. Factors such as gender, age, location, race, and access to necessities such as electricity, clean water and sanitation were additional factors used to calculate the MPI. Results indicate that individuals who are non-white, female, and who live in rural areas contribute the most towards poverty in South Africa. In order to check for robustness, a propensity score matching method (PSM) was used.. Results show that mobile money has a negative contribution to multidimensional poverty, that is, individuals who adopt mobile money have reduced rates of multidimensional poverty. The robustness demonstrated that mobile money has a positive and statistically significant effect on multidimensional poverty reduction.